Virgin Coconut Oil Inhibits Leukemic Cell Proliferation Via Apoptosis in K562 and MOLT-4 Cell Lines - Saosathan, Sawalee; Yodkeeree, Supachai; Warin, Arunrat; Duangnin, Natthachai; Peansub, Nittaya (Biomedical Sciences and Clinical Medicine, 2025)
Objective Leukemia is a blood cancer which is expressed by an uncontrolled increase in abnormal white blood cells. To date, chemotherapy has been regularly used to treat leukemia. However, the major problem with chemotherapy is the side effects for leukemia patients. Nowadays, medicinal plants are of interest as an additional form of cancer treatment. Virgin coconut oil (VCO) is a source of antioxidants, anti-viral, anti-inflammatory, and anti-cancer properties. This study was designed to investigate the potential of VCO to inhibit the growth of leukemic cells by inducing cell cycle arrest and apoptosis. Methods The VCO was analyzed using gas chromatography coupled with mass spectrometry (GC-MS). In the experiment, two leukemic cell lines, K562 and MOLT-4, were treated with various concentrations of VCO for 48 h. Cytotoxic effects were measured using the MTT assay and compared to commercial lauric acid. Cell cycle analysis was performed using propidium iodide (PI) staining, and apoptosis was assessed using an Annexin V-FITC kit. Results The study found that VCO is primarily composed of lauric acid, caprylic acid, capric acid, myristic acid, palmitic acid, linoleic acid, oleic acid, and stearic acid. In addition, VCO showed cytotoxic effects in both K562 and MOLT-4 cells, with IC50 values of 618.2 µg/mL and between 654 and 760 µg/mL, respectively. Cell cycle analysis demonstrated that VCO induced accumulation of cells in the G2/M phase. Additionally, the apoptosis assay demonstrated that VCO treatment induces apoptosis, particularly in K562 cells, in a cell-dependent manner. Conclusions VCO is a promising source of bioactive compounds which exhibit cytotoxic, cell cycle arrest and apoptotic effects on leukemic cells in-vitro, suggesting its potential for further investigation as an anti- leukemic agent.